Peculiar points in the phase diagram of the water-alcohol solutions - Chechko, V.E.; Gotsulsky, V.Ya.; Malomuzh, M.P. (Condensed Matter Physics, 2013)
The work is devoted to the investigation of nontrivial behavior of dilute water-alcohol solutions. The temperature and concentration dependencies of the contraction for aqueous solutions of ethanol and methanol are analyzed. The existence of a specific point, the so-called peculiar point, was established. It is shown that water-alcohol solutions of different types obey the principle of corresponding states if temperature and volume fraction are used as principal coordinates. In this case, the concentration of the peculiar point for different solutions is close to xν=0.28. Several predictions are made. Робота присвячена дослiдженню нетривiальної поведiнки розбавлених водно-спиртових розчинiв. Проаналiзовано температурнi i концентрацiйнi залежностi стиснення водних розчинiв етанолу i метанолу. Специфiчна поведiнка залежностей призводить до iснування особливої точки. Показано, що водно-спиртовi розчини рiзних типiв пiдкоряються принципу вiдповiдних станiв, якщо застосовувати в якостi основних координат температуру i об’ємну частку спирту. У цьому випадку особливостi рiзних параметрiв спостерiгаються в околi концентрацiй близьких до xν = 0.28. Зроблено декiлька прогнозiв.